Pengaruh Regulasi Emosi Terhadap Subjective Well-Being pada Guru SLB - Syaharani Galuh Shisilia; Mimbar Oktaviana (Departement of Mathematics Education, 2024)
This study aims to determine whether there is or there is no emotional regulation that affects the subjective well-being of Special School teachers in Surabaya. The population and sample in this study are all SLB teachers who meet the criteria of six Special schools in Surabaya. The Design research used in this research is non-experimental quantitative analysis. The method used in this study is a simple linear regression test to see whether emotional regulation affects subjective well-being or not. The total sample collected in this research is using purposive sampling. The instruments of emotional regulation and subjective well-being use questionnaires with a Likert scale approach. The results of the study showed a significance value = 0.001 (p<000.5) which means that there is an influence of emotional regulation on subjective well-being on SLB teachers in Surabaya with an r square value of 0.171 which means that emotional regulation has a positive influence on subjective well-being of 17.1%.